Buddy and Earl and the great big baby - Fergus, Maureen (Fergus, Maureen. Buddy and Earl, 2016)
Mom's friend Mrs. Cunningham is coming for a visit, and she's bringing her baby! While Buddy tries to explain the ins and outs of babydom to Earl, neither of them is prepared for the chaos the small and adorable creature brings with it. When the baby manages to escape from its cage-- which Buddy gently suggests is really just a playpen-- it's up to our favorite odd couple to save the day.